The Angular Distributions of Photoneutrons in Lead 206 and 208 Using Monochromatic Photons - Barkman, Nicholas John (My University, 1980)
In this work, an experiment to measure the angular distributions of neutrons generated in the (ϒ,n) reaction is described. Data are presented for the separated isotopes ²⁰⁶Pb and ²⁰⁸Pb and from the data analysis, the results are used to infer the extent of photon multipole mixing between 7 and 11 MeV, within the framework of the statistical collective nuclear model.
The experiment made use of an intense beam of highly monochromatic photons generated by neutron capture on nickel and chromium in the core of the McMaster Nuclear Reactor, and a high resolution Helium-3 neutron detector. Photoneutron spectra were recorded at seven angles between 20 and 160 degrees, and angular distribution functions were determined for all observed transitions.
Of considerable interest especially in ²⁰⁸Pb, is the question of M1 strength in the energy range of this experiment. The results of this work cannot confirm the existence of M1 strength, but evidence of multipole mixing, most likely E2: E1, was found at all photon energies. Estimates of the ratio of E2 to E1 strength are presented at all photon energies investigated for both lead isotopes.
Keywords: Physics; Physics